Protein and esterase patterns of pathogenic Fusarium oxysporum f. sp. elaeidis and F. oxysporum var. redlens from Africa and non-pathogenic F. oxysporum from Malaysia - Ho, Yin Wan; Varghese, George; Taylor, G. S. (Wiley, 1985)

(untitled)
Protein and esterase patterns of eleven isolates of F. oxysporum f. sp. elaeidis, one isolate of F. oxysporum var. redo/ens pathogenic to oil palm from Africa and six non-pathogenic isolates of F. oxysporum from oil palm soils in Malaysia were studied by vertical disc-electrophoresis and isoelectric focusing, to determine whether the pathogenic and saprophytic forms of F. oxysporum could be distinguished using these two methods. The protein patterns of all the isolates studied by the two methods were almost identical qualitatively and it was impossible to distinguish between the pathogenic isolates of F. oxysporum f. sp. elaeidis and F. oxysporum var. redo/ens from Africa and saprophytic isolates of F. oxysporum from Malaysia. Esterase zymograms of the isolates produced by the two methods were different. Esterase zymograms produced by vertical disc-electrophoresis showed great variations between and within the African and Malaysian isolates, but the esterase patterns produced by isoelectric focusing were almost identical qualitatively